Determinants of VAT rate: evidence from 27 EU countries - Martinho, Manuel Costa Pereira São (2016)
Tax rates have become a matter of public discussion since the 20th century. On one side population wants to maximize its utility by having a good purchase power that allows it to afford a basket of products and services that make it possible to have a good quality of life and. On the other side, government wants taxes to be on a level that maximizes tax revenue at the same time that it respects the interests of their people. Nowadays, Europe faces a situation of country convergence in a broad number of economic, social, and political factors. This convergence is caused or stimulated by the European Union legislation, by the interest of each country and also by automatic adjustments on people’s behaviour. One should note that the free mobility of goods, services, people and capital as well as the implementation of a common currency, for the applicable cases, is something that changed the path of Europe. When speaking about Europe one means countries, people and companies. Therefore, it is important to study the new trends of taxes and, more specifically, Value Added Tax. In order to perform a complete study for the European Union, this thesis compiles data from the 27 European Union countries from the year 2005 to 2012, for which 15 different variables related to different fields are used. The results indicate that a rise in Consumption raises the VAT Rate, while rises in Compliance Rate and GDP per capita lower the VAT Rate instead.